2023
DOI: 10.3390/biom13050838
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress in Calcitonin Gene-Related Peptide and Bone Repair

Abstract: Calcitonin gene-related peptide (CGRP) has 37 amino acids. Initially, CGRP had vasodilatory and nociceptive effects. As research progressed, evidence revealed that the peripheral nervous system is closely associated with bone metabolism, osteogenesis, and bone remodeling. Thus, CGRP is the bridge between the nervous system and the skeletal muscle system. CGRP can promote osteogenesis, inhibit bone resorption, promote vascular growth, and regulate the immune microenvironment. The G protein-coupled pathway is vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 136 publications
0
7
0
Order By: Relevance
“…Factors listed have been shown to promote bone formation and/or improve fracture healing. Most factors promote osteogenic expression, although VIP has shown thus far to only inhibit OCs Molecular factor Primary receptor(s) Function in bone CGRP CLR and RAMP1 [ 38 ] ↑ osteogenic gene expression [ 38 ] SP NK-1R [ 39 ] ↑ osteocalcin and collagen expression [ 39 , 40 ] VIP VPAC1 and VPAC2 [ 41 , 42 ] ↓ OC differentiation [ 41 , 42 ] NPY Y1 [ 43 ] ↑ RUNX2 expression in MSCs [ 43 ] BDNF* TrkB [ 44 ] ↑ OPG expression [ 44 ] NGF* TrkA [ 20 , 45 ] ↑ BMP and VEGF expression [ 46 , 47 ] *Not made endogenously by peripheral nerves …”
Section: Molecular Factors In Peripheral Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Factors listed have been shown to promote bone formation and/or improve fracture healing. Most factors promote osteogenic expression, although VIP has shown thus far to only inhibit OCs Molecular factor Primary receptor(s) Function in bone CGRP CLR and RAMP1 [ 38 ] ↑ osteogenic gene expression [ 38 ] SP NK-1R [ 39 ] ↑ osteocalcin and collagen expression [ 39 , 40 ] VIP VPAC1 and VPAC2 [ 41 , 42 ] ↓ OC differentiation [ 41 , 42 ] NPY Y1 [ 43 ] ↑ RUNX2 expression in MSCs [ 43 ] BDNF* TrkB [ 44 ] ↑ OPG expression [ 44 ] NGF* TrkA [ 20 , 45 ] ↑ BMP and VEGF expression [ 46 , 47 ] *Not made endogenously by peripheral nerves …”
Section: Molecular Factors In Peripheral Regulationmentioning
confidence: 99%
“…CGRP is a polypeptide primarily known for its nociceptive signaling as a neurotransmitter and as a vasodilatory, proangiogenic molecule [ 38 ]. Its main receptors are the calcitonin gene-related peptide receptor (CLR) and receptor activity modifying protein 1 (RAMP1).…”
Section: Molecular Factors In Peripheral Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcitonin gene related peptide is a members of the calcitonin family, mainly it is a nociceptive neurotransmitter acting on one of two receptors: calcitonin gene-related peptide receptor (CLR) and receptor activity modifying protein 1 (RAMP1) ( 93 ). CGRP plays a crucial role in bone fracture healing, in a study that collected plasma from patients with fracture neck of femur it was found to be highly elevated after 24 h compared to healthy controls ( 69 ).…”
Section: Growth Factors For Nerve Regenerationmentioning
confidence: 99%
“…[ 15 ] The sensory nerve fibers containing CGRP are distributed abundantly among bone, periosteum, epiphysis, bone marrow, and they make a strong effect on osteoblasts. [ 16 ] Because of the direct function on osteoblasts, we suspected that neuropeptides may make a certain contribution to osteophyte formation, and this is a question which has not been looked into adequately to date.…”
Section: Introductionmentioning
confidence: 99%